2021
DOI: 10.1177/20494637211023074
|View full text |Cite
|
Sign up to set email alerts
|

What is the content of virtually delivered pain management programmes for people with persistent musculoskeletal pain? A systematic review

Abstract: Introduction: Virtual consultations (VC) have been embraced by healthcare organisations during the COVID-19 pandemic. VC allows continuation of patient care while adhering to government advised restrictions and social distancing measures. Multidisciplinary pain management programmes (PMPs) are a core element of many pain services and utilising virtual methods to deliver PMPs has allowed them to continue to provide care. This systematic review aimed to explore the content of existing virtually delivered PMPs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…We found no studies reported in the literature that used the BPS guidelines to support the design of vPMPs. 6 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found no studies reported in the literature that used the BPS guidelines to support the design of vPMPs. 6 …”
Section: Resultsmentioning
confidence: 99%
“…and D.W.). 6 The purpose of which was to identify the variation in content of virtually delivered PMPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that there were also significant contextual factors occurring during the COVID19 pandemic that may well have impacted upon outcomes, either as mediators or moderators of treatment effects. Whilst there is evidence that virtual formats can be effective therapeutic formats for the delivery of pain management programmes 1,18 and psychological therapy 27,28 further research would be required to understand the relative contribution of format and contextual factors to CFT-PM outcomes during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…CLBP frequently coincides with Kinesiophobia, creating a cycle of pain avoidance and physical deconditioning ( 20 ). Exploring how Kinesiophobia might mediate the relationship between limits of stability (LOS) and functional balance provides critical insights into the mechanisms contributing to functional impairments in CLBP patients ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%